Percentiles of serum uric acid and cardiometabolic abnormalities in obese Italian children and adolescents - Luciano, Rosa (Ital J Pediatr, 2017)
BACKGROUND: To investigate the association of serum uric acid (SUA) with cardiometabolic abnormalities in Caucasian overweight/obese children (<10 years of age) versus adolescents (≥10 years of age) by drawing age and gender specific percentiles of uric acid. METHODS: Cross-sectional evaluation of 1364 Caucasian overweight/obese patients (age 4.1–17.9 years; 726 males, 53%; 560 children, 41%). RESULTS: SUA levels were significantly lower in children than in adolescents (4.74 ± 1.05 vs. 5.52 ± 1.49 mg/dl, p < 0.001) and peaked in 12–14 years-old boys and 10–12 years-old girls. In children with levels of SUA in the highest quartile (N = 75, 13%), OR for high triglycerides was 4.145, 95% CI 1.506–11.407 (p = 0.009). In adolescents with SUA in the highest quartile (N = 274, 34%), ORs for insulin resistance was 2.399 (95%CI 1.4–4.113; p < 0.001); for impaired fasting glucose 2.184 (95% CI 0.877–5.441; p = 0.07); for impaired glucose tolerance 2.390 (95% CI 1.405–4.063; p = 0.001); and for high triglycerides 1.8, (95%CI 0.950–3.420; p = 0.05). Multivariable random-effect linear regression models demonstrated that waist circumference and age (p < 0.0001 for both) are the variables most significantly predicting SUA levels, followed by triglycerides (p = 0.005) and 2 h glucose (p = 0.03) while HOMA-IR and BMI z-score did not predict SUA. CONCLUSIONS: High uric acid is associated with metabolic abnormalities and particularly with waist circumference very early in childhood.